2013
DOI: 10.1136/oemed-2012-101005
|View full text |Cite
|
Sign up to set email alerts
|

Depressive symptoms and severity of acute occupational pesticide poisoning among male farmers

Abstract: Our findings suggest that the risk of depression appears to be related to the severity of symptoms of poisoning, type of care received and the number of previous episodes of acute poisonings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
27
0
4

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 43 publications
(36 citation statements)
references
References 37 publications
5
27
0
4
Order By: Relevance
“…Furthermore, it has been suggested that the exposure to high levels of pesticides, including poisoning, experienced by agriculture workers and rural residents may result in an elevated risk of neuropsychiatric sequelae such as mood disorders, depression, and suicide attempts [32], [33]. Recently, we found that depressive symptoms [34] and suicidal ideation [35] were significantly associated with a history of acute occupational pesticide poisoning and that this relationship was further associated with the severity of the symptoms of poisoning among Korean male farmers.…”
Section: Discussionmentioning
confidence: 94%
“…Furthermore, it has been suggested that the exposure to high levels of pesticides, including poisoning, experienced by agriculture workers and rural residents may result in an elevated risk of neuropsychiatric sequelae such as mood disorders, depression, and suicide attempts [32], [33]. Recently, we found that depressive symptoms [34] and suicidal ideation [35] were significantly associated with a history of acute occupational pesticide poisoning and that this relationship was further associated with the severity of the symptoms of poisoning among Korean male farmers.…”
Section: Discussionmentioning
confidence: 94%
“…Those who had experienced occupational pesticide poisoning had a higher risk of experiencing symptoms. The risk was even higher with more severe poisoning, in cases where the victim had visited medical institutions, or had multiple poisonings [27]. Therefore, providing early detection and treatment for pesticide poisoning victims is crucial for preventing depression.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to this self-report questionnaire, a more objective judgment of depressive symptoms was attempted by extracting the depression index from the short version of the Geriatric Depression Scale, which consists of 15 items (GDS-15). For the GDS-15, scoring is conducted by assigning 1 point to each affirmative response to 10 items and 1 point to each negative response to 5 items; a total depression score <5 is considered normal, and scores of 5 to 7 and ≥8 suggest suspected and demonstrated depression, respectively [ 11 - 13 ]. The questionnaire used in this study was also used for the survey on health effects of environmental exposure in the elderly population conducted by the National Institute of Environmental Research, the quality of which has been verified in a number of studies.…”
Section: Methodsmentioning
confidence: 99%